Dendritic Chemistry Applied to the Construction of Tailored Functional Nanomaterials: Synthesis and Characterization of Gold Nanoparticle-Cored Dendrimers (NCDs) - Paez, Julieta Irene (2013)
A family of Newkome-type dendritic molecules bearing a disulfide anchor group, different peripheral groups (-COOtBu or -COOH) and sizes or generations (Gn=0-2) was synthesized and used as ligand for the synthesis of gold nanoparticle-cored dendrimers (NCDs). These hybrid materials were characterized by means of UV-vis spectroscopy, TEM, and IR and NMR spectroscopies, finding that the capping molecules of the organic shell determine the solubility and stability of the different NCDs, as well as the characteristics of the inorganic core through a dendritic control characteristic for Newkome-type ligands. Remarkably, a combination of detailed IR and NMR studies allows for studying the ligand-ligand and ligand-core interactions that take place in these materials. It is demonstrated that concepts, techniques and methods normally used in organic and dendritic chemistry, such as the synthesis of precisely controlled architectures and their rigorous spectroscopic characterization, can be efficiently applied to engineer novel organic-inorganic hybrid materials with enhanced properties.